Content of Short-Lived Radionuclides (54Mn, 60Co, and 65Zn) in Fish - Nataliia E. Zarubina; Vladislav Semak; Liliia P. Ponomarenko; Oleg S. Burdo (Fishes)
This review summarizes data on the accumulation of three short-lived biogenic radionuclides—54Mn, 60Co, and 65Zn—in various fish species in the cooling pond of the Chornobyl Nuclear Power Plant in Ukraine, along with an analysis of the available literature. Significant differences exist in 54Mn, 60Co, and 65Zn accumulation levels among the different fish species. Food intake is the primary pathway for these radionuclides to enter the fish organisms. These radionuclides accumulate differently in various organs and tissues. There is no consensus on the specific organ that primarily accumulates each radionuclide. In most studies, the highest concentrations of 54Mn have been recorded in internal organs. The kidneys are identified as the main organ accumulating 60Co. The highest concentrations of 65Zn are typically found in the liver and kidneys; however, significant accumulation is also noted in external organs and tissues (gills, fins). In most cases, the lowest concentrations of 54Mn, 60Co, and 65Zn are observed in the muscle tissues of fish.